(untitled) (مجلة البحوث الأكاديمية, 2021)
In this article, we survey some elementary techniques for understanding the invariant theory of finite groups with emphasis on symmetric groups, and give an overview of a package for WxMaxima, called sym which contains tools for writing invariants in terms of many bases.